Comunidades de macroinvertebrados acuáticos y su relación con los usos de suelo en la calidad hídrica de los esteros Lampa, Primavera y Villavicencio, cantón Valencia, Ecuador - Loor Lucas, Juan Alexander (2020)
This study was conducted in micro-cuencas Lampa, Primavera, Villavicencio of the canton Valencia, Ecuador. In which three land use coverages (Forest, Urban and Agriculture) were assessed through aquatic macroinvertebrate communities to determine the status of water resource quality. The River Habitat Index (IHF), Forest and Rivera Quality Index (QBR) is applied. In addition, the Anova kruskal- Walls’s analysis program evaluated Simpson (dominance), Shannon (diversity), and Pielou (equity), and cruster analysis to evaluate the composition and structure of macroinvertebrates. As a complement, redundancy analysis was applied to evaluate both the most representive genera (Erithrodiplax, Ishnura, Caenis Stephen, Baetodes, Philogenia and Camelobaetidius), and chemical physical parameters (pH, Temperature, Electrical Conductivity, Dissolved Oxygen, Total Dissolved Solids). The following results were obtained from the points monitored every 15 days in December, January and February 2020-2021, 8 orders 25 families and 29 genera resulting in 1151 individuals, among them are the following: the order Odonata of the family Coenagrionidae of the genus Ishnura with (31.71%), the order Ephemeroptera of the family Baetidae with two genera Baetodes with (20.85%) And Camelobaetidius with (7.12%) Respectively. Moreover, the least predominant family found in soil uses is: the Trichoptera order of the Philopotamidae family of the genus Chimarra with a single found individual representing (0.41%). In the application of the BMWP-Cr index on a quarterly basis, it was determined that the water quality for forest soil cover and agriculture is of "poor, contaminated quality" and in the urban area the 1.3 "bad quality, contaminated" and section 2 "very polluted". Keywords: coverages; macro-vertebrates; IHF, QBR, BMWP-Cr; water quality.